Peroperative Local Anesthetic Bupivacaine Infiltration Prevent Postoperative Pain in Lumbar Disc Herniectomy - Yucetas, Seyho Cem; Mordeniz, Cengiz; Ucler, Necati; Baran, Onur; Varol, Gamze (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Background: Lumbar discectomy has been one of the most common surgical practices performed by neurosurgeons as the complete treatment even though recently a trend against surgery appeared since many patients still suffer from pain after surgery and are not able to return to their daily physical activities. Insufficient pain treatment increases postoperative pain and complaints and the recovery is longer. Aim: This study aims to search if peroperative levobupivacaine infiltration over the dorsal root can prevent postoperative pain. Materials and Methods: This study was performed between February 2010 to May 2012 in the Neurosurgical Department of Adiyaman Research and Application Hospital, in Turkey, among 120 patients who were operated on for lumbar disc herniectomy. All the patients were followed for the postoperative 72 hours. Half of them were given peroperative levobupivacaine (2 cc) on the related dorsal root, and the other half received serum physiologic (2 cc). After ten minutes, the operation continued. Postoperatively, the analgesic requirements of the patients were followed for 72 hours. The data is analyzed with Kolmogorov-Smirnov analysis to check normal distribution. The data was convenient (p>0.05). For the statistics, SPSS 15.0 was used. Measurable data was analyzed with student t-test and the comparison was made with chi-square. The data was evaluated in the confidence interval of 95% for both directions. Results: In the study, 80 of the patients were female and 40 were males. The patients in the control group required analgesia immediately after the operation but in the levobupivacaine group the earliest analgesic requirement was after 4 hours, but some of the patients did not need any analgesic even up to 50 hours. Conclusion: Most of the patients undergoing lumbar disc herniectomy usually suffer from significant severe back pain. This study propose that peroperative local anesthetic infiltration has significantly reduced postoperative analgesic requirement.